Online in the Students' Learning-Teaching Process Midwifery During the Covid-19 Pandemic - Popy Apriyanti; Apriyanti Aini (GLOBAL HEALTH SCIENCE GROUP, 2022)
The Covid-19 pandemic has disrupted the learning process in universities, especially in conventional health universities. So a solution is needed to answer this problem. Online learning is one alternative that can overcome this problem. The purpose of this study was to determine the relationship between the effectiveness of online learning methods and obstacles in the teaching and learning process during the covid-19 pandemic. This type of research uses cross sectional. The research time is from March 29 to April 7, the population of this study is 30, namely the sampling using purposive sampling with a sample of 30 respondents. Data collection using a questionnaire. Based on the results of the chi-square test in table 4.3 above, the p value = (0.66) is greater than = 0.05 (p value) this shows that there is no significant relationship between the effectiveness of online learning methods and obstacles in the teaching and learning process during the covid-19 pandemic.